2007
DOI: 10.1111/j.1445-2197.2007.04116_11.x
|View full text |Cite
|
Sign up to set email alerts
|

Cr11
patient Recall of Informed Consent Information Prior to Colonoscopy

Abstract: Purpose  To determine if patients presenting for colonoscopy can remember information discussed in the informed consent process. Focusing on whether patients know of the possible risks. Methodology  A prospective study of patients presenting for elective colonoscopy through the Colorectal Unit. Patients were consented in outpatient clinics prior to the procedure using the colonoscopy consent form supplied by Queensland Health. On the day of the procedure a 2 page questionnaire with 13 questions was completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, some controversies remain about the appropriateness of the current informed consent procedure prior to gastrointestinal endoscopy and its acceptance and understanding by patients. A previous study showed that the current consent process was inadequate for educating patients about the possible serious risks involved and about other therapeutic options [ 4 ]. Additionally, a survey performed in the UK showed that the consent procedures appeared to fall short of the ideal, particularly with regard to information about procedural risks and allowing patients sufficient time to make informed decisions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some controversies remain about the appropriateness of the current informed consent procedure prior to gastrointestinal endoscopy and its acceptance and understanding by patients. A previous study showed that the current consent process was inadequate for educating patients about the possible serious risks involved and about other therapeutic options [ 4 ]. Additionally, a survey performed in the UK showed that the consent procedures appeared to fall short of the ideal, particularly with regard to information about procedural risks and allowing patients sufficient time to make informed decisions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%